Expansive Soil Stabilization Using Lime and Bottom Ash to Increase the CBR Value: A Case of Cililin Soil - Ahmad Fauzi Setiawan; Erlangga Rahadian; Geni Firuliadhim; Bayu Wintoro (Department of Civil Engineering, Politeknik Negeri Bandung, 2025)
Soil stabilization plays a crucial role in enhancing the bearing capacity of soils to support structural loads, particularly in road construction projects involving soft soils with inherently low strength. This study investigates the feasibility of using bottom ash, a coal industry waste, as a soil stabilizing agent. Utilizing bottom ash not only aims to improve soil mechanical properties but also addresses environmental concerns associated with coal waste disposal. Laboratory tests were conducted to evaluate the index properties (specific gravity, Atterberg limits, and grain size distribution) and engineering properties (compaction characteristics, swelling behavior, and unconfined compressive strength) of soil treated with varying proportions of bottom ash. The results demonstrate that the addition of bottom ash significantly enhances the soil’s bearing capacity and reduces swelling potential, indicating its suitability for application as a subgrade layer in pavement construction. The addition of 13% lime combined with varying percentages of bottom ash significantly improved the soil’s properties, with CBR values increasing to between 11% and 15%, compared to the untreated soil. This study highlights the potential of bottom ash as an effective and sustainable soil stabilizer, contributing to both infrastructure development and industrial waste management.